LMX Theory: Quality of Relationships and Organizational Climate in Research Centers of Sweetener and Fiber Plants, 2010−2019 - Farikha Rachmawati; Isni Tri Lestari (LPPM Stikosa - AWS, 2023)
The quality of the relationship between superiors, subordinates, and colleagues is strongly influenced by organizational climate. Organizational communication problems that occur repeatedly, the lack of communication between superiors and subordinates, and conflicts at the employee level make the basis for researchers to conduct research and try to provide recommendations to improve conditions within the Balittas organization. This research will discuss the quality of the relationship between superiors, subordinates, and colleagues from 2010-2019. This study aims to identify and analyze the quality of the relationship between superiors and subordinates, between coworkers for each period of each leader, analyze the implications of leadership communication styles on the quality of the relationship between leaders and subordinates and among colleagues. This research was conducted using the Action Research method to go to Balittas from 2010 to 2019. Based on constructivism paradigm, this study collected data using structured interviews and analyzed using the action research cycle from Coghlan and Brannick. The results of this study indicate that the quality of the relationship between superiors and subordinates, as well as coworkers, is influenced by the leadership's communication style and communication climate The quality of the relationship between superiors and subordinates, between colleagues in each period of each leader based on the LMX Theory, is dominated by our group quality. This is because the relationship bond is only limited to a contractual bond. The leader's communication style has implications for the quality of organizational member relationships. Subsequent research can develop the application of LMX theory in other government work units and create efforts to build quality in-group relationships within Balittas